More than they could chew: activity‐induced dental modifications in a portuguese medieval–modern rural population - Neves, Dulce (2022)
Non-masticatory dental lesions (e.g., notching, interproximal grooving, polished surfaces, lingual tilting, and dental trauma) may help evaluate the impact that dietary, individual, or social-cultural habits had on ancient populations. Thus, this study aims to describe and discuss possible causes for dental wear and trauma recorded in 1206 commingled teeth recovered from a medieval-modern ossuary in Miranda do Corvo (Coimbra, Portugal). All teeth were observed macroscopically under good light conditions. Dental wear and traumatic injuries were recorded according to their location. Atypical wear was divided into five categories—notches and grooves, polished surfaces, oblique wear plane, interproximal grooves, and lingual tilting. Higher mean values of occlusal dental wear were found in the anterior dentition (3.03 ± 1.457; n = 396), being the central incisors the more worn out (3.19 ± 1.28; n = 102). In all, 11.0% of the observed teeth presented atypical wear (130/1185), being anterior teeth (26.7%; 112/419) more affected than posterior (17.0%; 128/765). The most common alterations were notches/grooves (50.0% of the teeth with atypical wear; 65/130) and dental microtrauma (20.3% of the observed teeth; 240/1184). Furthermore, teeth presenting microtrauma were more affected by atypical wear, affecting 38.9% (48/130) of the worn teeth. An association between chipping and notches and/or grooves (62.5%; 30/48) was also noted. The obtained results, namely, the morphology and distribution of the “incisor-dominant” dental wear and dental trauma patterns, suggest that many individuals of this population may have used their teeth as a “third hand” in routine practices. However, some types of atypical wear, namely, polished lingual surfaces of anterior teeth, may have had other causes, such as malocclusion. This study provides new insights into how ancient populations used their dentitions, even when the osteological remains are recovered from a commingled context.